Constructing a pedagogical third space with multilingual children: A case study of the bilingual Stars of Today Literacy Club# (STLC#) - Guzula, Xolisa (School of Education, 2022)
This thesis was motivated by my own family's language biography, and the social justice work I have been doing over the years in bi-multilingual education. This work has involved challenging the continuation of Apartheid language in education policy in practice in schools for Black African language speaking children, the neglect of the multilingual Language in Education Policy of 1997, and the narrow perspective on literacy learning in the Curriculum and Assessment Policy Statement enforced by the Department of Basic Education and the provincial departments of education. Connected to the continuing subtractive, Anglonormative, monoglossic and monolingually oriented bilingual language in education policy in practice, which teaches languages in silos as Home and First Additional Languages, is the deficit construction of Black African language - emergent English speaking bi-multilingual children. This study argues that the curriculum's construction of separate Home and Additional Language periods continues to be calibrated to the needs of White English and Afrikaans monolingual children who speak one language at home, learn it at school as Home Language, and a second language as a First Additional Language. This same policy is imposed on Black bi/multilingual children, largely regarding as problematic their rich linguistic repertoire and language resources. This deficit positioning of these children inspired me to start an intervention which involved facilitators and children in co-constructing a multilingual and multimodal literacy club as a third space that calibrated language and literacy learning to their multilingual needs and to research this intervention. My research aimed to answer the questions: How is a bi-multilingual, multimodal third space co-constructed in an after-school literacy club? How do children from marginalised communities conceptualise language and literacy learning? What are the affordances of a bi/multilingual and multimodal approach to language and literacy learning in an out-of-school literacy club? And how do children respond to a bi/multilingual, multimodal pedagogical approach which legitimises all the semiotic resources in their repertoire? To answer these questions, I drew on linguistic ethnography as my methodology. The findings show, first, that bi/multilingual children learning language and literacy desire and need the affective, social, and linguistic third spaces, physical third spaces and pedagogical spaces that value and legitimise their sociocultural resources and include their full semiotic repertoire. Thus, the literacy club, instead of perpetuating binaries, was created as a pedagogical third space that legitimised both translanguaging pedagogy and spontaneous translanguaging for meaning making. Though facilitators might plan for pedagogical translanguaging in activities to take place in any of the languages used for teaching and learning in a bilingual learning space, the children spontaneously translanguaged, and drew on their hybrid linguistic repertoire for meaning making even in tasks that required them to work monolingually, in many cases producing bilingual texts. Their meaning making processes while engaging with the activities demonstrated that emergent bilinguals are at different stages in the bilingual and biliteracy continuum, and that drawing from their hybrid repertoire helps them participate and engage meaningfully with the activities. Secondly, the findings show that multilingual languaging on its own is not sufficient for meaning making, and multimodal communication alongside their use of their multilingual repertoire enriches children's meaning making. Drawing on a full semiotic repertoire creates a third space that does not just transcend language and non-verbal communication: it creates education opportunities that build on children's sociocultural resources. These include knowledges, languages and discourses, and ways of seeing, doing, reading, and writing the world. Thirdly, the study shows that language and literacy learning require both pedagogised literacy and social uses of literacy, thus transcending both autonomous and sociocultural understandings of literacy. Finally, collaborative activities were shown to be central in both multilingual and multimodal communication. These also allow for a distributive system of skills that children bring to their language and literacy activities. This multiple languaging and collaborative process not only enriches their final written product in whatever named language the activity is assigned but creates an affective social space that takes away the pressure and stress often placed on individual learners who are forced to compete. Additionally, drawing on their multilingual and multimodal repertoires assists children in achieving cognitively demanding tasks, including translation. Translation, interpreting, multiple languaging, and metalinguistic awareness are higher order skills that create opportunities for children to think deeply about the task at hand, make explicit their thinking processes by engaging in exploratory talk, and write to express what they know and feel.